Topographical anatomy of the subthalamic region with special interest in the human medial forebrain bundle - Meszaros, Cintia; Kurucz, Peter; Baksa, Gabor; Alpar, Alan; Ganslandt, Oliver; Brandner, Sebastian; Barany, Laszlo (Journal of Neurosurgery, 2024)
OBJECTIVE The medial forebrain bundle (MFB) is a novel promising deep brain stimulation (DBS) target in severe affective disorders that courses through the subthalamic region according to tractography studies. Its potential therapeutic role arose in connection with the development of hypomania during stimulation of the subthalamic nucleus (STN) in Parkinson's disease, offering an alternative explanation for the occurrence of this side effect. However, until now its course exclusively described by tractography had not yet been confirmed by any anatomical method. The aim of this study was to fill this gap as well as to provide a detailed description of the fiber tracts surrounding the STN to facilitate a better understanding of the background of side effects occurring during STN DBS. METHODS Ten human cadaveric brains (20 hemispheres) and 100 healthy subjects (200 hemispheres) from the S500 Release of the Human Connectome Project were involved in this study. Nineteen hemispheres were dissected according to Klingler's method. One additional hemisphere was prepared for histological examinations to validate the macroscopical results and stained with neurofibril silver impregnation according to Krutsay. The authors also aimed to reconstruct the MFB using tractography and correlated the results with their dissections and histological findings. RESULTS The white matter connections coursing through the subthalamic region were successfully dissected. The ansa lenticularis, lenticular fasciculus, thalamic fasciculus, ipsi- and contralateral cerebellar fibers, and medial lemniscus were revealed as closely related fiber tracts to the STN. However, the existence of a distinct fiber bundle corresponding to the MFB described by tractography could not be identified. Using tractography, the authors showed that the depiction of the streamlines representing the MFB was also strongly dependent on the threshold parameters. CONCLUSIONS According to this study's findings, the streamlines of the MFB described by tractography arise from the limitations of the diffusion-weighted MRI fiber tracking method and actually correspond to subthalamic fiber bundles, especially the ansa lenticularis and lenticular fasciculus, which erroneously continue in the anterior limb of the internal capsule, toward the prefrontal cortex.
CRIS-Team Scopus Importer:2024-08-16
Keywords: anatomy; deep brain stimulation; fiber dissection; functional neurosurgery; medial forebrain bundle; subthalamus; tractography